2007
DOI: 10.1080/13598130701350593
|View full text |Cite
|
Sign up to set email alerts
|

Giftedness and evidence for reproducibly superior performance: an account based on the expert performance framework

Abstract: Giftedness researchers have long debated whether there is empirical evidence to support a distinction between giftedness and attained level of achievement. In this paper we propose a general theoretical framework that establishes scientific criteria for acceptable evidence of superior reproducible performance, which any theory of exceptional performance must explain. We review evidence for superior reproducible performance, generally emerging only after extended periods of deliberate practice that result in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(38 citation statements)
references
References 174 publications
1
33
0
1
Order By: Relevance
“…Consequently, coaches and athletes may benefit from adopting strategies such as beginning with easy plays. While the importance of progressing from simpler tasks to more complex ones is unambiguous in the process of motor skill learning (Ericsson, Roring, & Nandagopal, 2007), we did not find previous research that showed that the same applied to the execution of tasks in performance settings. Therefore, to our knowledge, the findings of this study are the first to report the importance of beginning with easy plays in performance settings as a way to prevent early mistakes from causing distractions.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, coaches and athletes may benefit from adopting strategies such as beginning with easy plays. While the importance of progressing from simpler tasks to more complex ones is unambiguous in the process of motor skill learning (Ericsson, Roring, & Nandagopal, 2007), we did not find previous research that showed that the same applied to the execution of tasks in performance settings. Therefore, to our knowledge, the findings of this study are the first to report the importance of beginning with easy plays in performance settings as a way to prevent early mistakes from causing distractions.…”
Section: Discussionmentioning
confidence: 94%
“…For example, the movie critics who vote on the National Board of Review Awards (and the industry members who vote on the Academy Awards) have a much higher level of expertise than the average layperson. Both the critics and the professionals have spent years either making or evaluating movies, comparable to the 10 years of deliberate practice needed to make a substantial contribution to a field (Ericsson, Roring, & Nandagopal, 2007). Most laypeople, however, are novices.…”
mentioning
confidence: 99%
“…Aqueles que se fundamentam nessa perspectiva defendem que para um indivíduo concluir a última etapa e se tornar especialista, são necessários, no mínimo, 10 anos de exercício recorrente ou 10.000 horas de prática (Ericsson, 2004;Ericsson, Roring, & Nandagopal, 2007). Os resultados do treinamento podem ser facilitados (mas não acelerados) quando o indivíduo apresenta disponibilidade, motivação, tem acesso a mentores especializados e materiais adequados e inicia cedo na área de atuação (Ericsson, 2004).…”
Section: Talento Como Resultado Da Prática Deliberada (Ou Expertise)unclassified